Answer:
![y=27](https://img.qammunity.org/2023/formulas/mathematics/college/aerkpvzhgycfowjuaoj1uvx9n8mtac4nvk.png)
Step-by-step explanation: The statement y varies with the square of x and be translated into mathematics as follows:
![y\propto x^2](https://img.qammunity.org/2023/formulas/mathematics/college/ev2isem75zkkaaqeolezh4xqdf3esoax7y.png)
The statement implies that there is a proportional relationsip:
![y=k\cdot x^2\rightarrow(1)](https://img.qammunity.org/2023/formulas/mathematics/college/6y5frfvnda3ip47h8lhozmrzqi6hotet14.png)
Using the condition that y = 12 when x = 2 we can calculate the value of k for the equation (1) as follows:
![\begin{gathered} 12=k\cdot(2)^2 \\ k=(12)/((2)^2)=(12)/(4)=3 \\ k=3 \\ \therefore\rightarrow \\ y=3\cdot x^2\rightarrow(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6f5kyzzim0bbr577qlk3bcn1up6pm5u4rr.png)
Finally, the value of y when the x = 3 is as follows:
![\begin{gathered} y=3\cdot(3)^2 \\ y=3\cdot9 \\ y=27 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1k8ununekak8h5ieg27icyhxm24mzd8y3g.png)
Conclusion: Therefore when x = 3 the y = 27